The Development and Validation of Questionnaire on Autism Spectrum Disorders and its Association With Plastic-Based Food Contact Materials - Nor, Zaleha Md; Isa, Zaleha Md; Yusof, Siti Norbayah; Ghazi, Hasanain Faisal; Jaafar, Mohd. Hasni (Journal of Nepal Paediatric Society, 2018)
Introduction: Autism is a neuropsychiatric disorder. Multiple factors have been identified as causes of autism spectrum disorder. Many studies indicated genetic as the main risk factor, but environmental risk factors are also seen as contributing factors. Exposure to environmental pollutants such as endocrine disrupting chemicals (EDCs) can occur as early as in the mother’s womb. The main concern of EDCs in food packaging are Bisphenol A (BPA) and phthalates. The objectives of this study are to develop and validate a questionnaire for the assessment of habitual usage of plastic- based food contact materials (FCM) as a proxy for exposure to this group of EDCs. Material and Methods: The questionnaire developed by organising a focus group discussion among experts. An interview-guided pilot study was then done to 250 respondents for construct validation process. In the validation process, test-retest study for reliability, Cronbach alpha for internal consistency, exploratory factor analysis and confirmatory factor analysis were done. Results: The questionnaire achieved kappa value ranged between 0.800 to 0.900 for knowledge, 0.610 to 0.815 for perception and 0.607 to 1.000 for self-care product section. Cronbach alpha value ranged between 0.600 to 0.780. Conclusions: Exploratory and confirmatory factor analysis approved the final model for phase one consisting of four domains with total of 13 items and final model for phase two consists of three domains with total of nine items.